Мастера и шедевры: в 6 томах (Игорь Долгополов) - Долгополов Игорь (2008)
Экземпляры: ф.14 (2008) / Инвентарный номер: zzzzzz87 / Цена: / Сис.шифр: 85.143(3) / Авт.знак: Д 64 / ГРНТИ: 18.31.91 / ББК: 85.143(3)